2015
DOI: 10.3390/ijms160612531
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D3 Levels, BsmI Polymorphism and Insulin Resistance in Brazilian Amazonian Children

Abstract: Vitamin D is associated with a wide range of other functions beyond bone development. We evaluated the factors associated with 25-hydroxyvitamin D levels in 974 children aged ≤10 years and the impact of BsmI polymorphism of the vitamin D receptor (VDR) gene (rs1544410) on metabolic parameters in a subsample (n: 430) with a follow-up 2 years later from the initial population-based cross-sectional study. Multiple linear regression models were used in the analyses. The prevalence (95% CI) of vitamin D deficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
(67 reference statements)
3
23
0
4
Order By: Relevance
“…The A allele itself was significantly associated with vitamin D deficiency in our population. Our finding is consistent with studies on Brazilian children where BsmI polymorphism was found to be associated with serum vitamin D level [26, 28] although it was the wild variant (GG) that was associated with lower vitamin D levels in Brazilian girls [26]. In contrast, the association between BsmI polymorphism and vitamin D levels was not supported in other populations such as the Arabs (Saudi) [38], Uygur and Kazakhs [39] as well as the European adolescents [40], suggesting that this SNP may influence vitamin D levels rather differently in different population.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The A allele itself was significantly associated with vitamin D deficiency in our population. Our finding is consistent with studies on Brazilian children where BsmI polymorphism was found to be associated with serum vitamin D level [26, 28] although it was the wild variant (GG) that was associated with lower vitamin D levels in Brazilian girls [26]. In contrast, the association between BsmI polymorphism and vitamin D levels was not supported in other populations such as the Arabs (Saudi) [38], Uygur and Kazakhs [39] as well as the European adolescents [40], suggesting that this SNP may influence vitamin D levels rather differently in different population.…”
Section: Discussionsupporting
confidence: 93%
“…However, when insulin resistance was examined as a categorical variable with the cut-off for HOMA-IR chosen based on pubertal stage [32], it was found that the AA genotype of BsmI conferred higher risk of insulin resistance as compared to the GG genotype. The cohort of Brazilian children also reported to demonstrate association between this SNP and insulin resistance [28]. Thus, our study highlights the possible role of VDR BsmI polymorphism in mediating insulin resistance in early adolescence in non-Caucasian populations.…”
Section: Discussionsupporting
confidence: 69%
“…19 El porcentaje de niños con niveles inferiores a 30 ng/mL (75 mmol/L) de vitamina D en el AMB fue 46.38%, con diferencias significativas entre los diferentes municipios en un rango entre 60.00% y 32.43%, mostrando tanta variabilidad como la encontrada a nivel regional para la población infantil o adolescente. En el estudio de Bogotá, por ejemplo, 56.57% de los niños de 5 a 12 años tenían insuficiencia o deficiencia de la vitamina D; 8 en Costa Rica, de 616 niños entre 6 y 14 años evaluados, 28% tenía niveles inferiores a 30 ng/ mL; 7 en Brasil, la deficiencia o insuficiencia en niños menores de 10 años fue de 32.9% (n=974); 20 en México, en 1 025 niños de 2 a 12 años se reportaron deficiencias en 54% de los preescolares y 28% de los escolares; 21 en Estados Unidos, 9% de la población pediátrica presenta deficiencias de 25-OH-D y 61% insuficiencias, de acuerdo con lo reportado por el NHANES 2001-2006 (National Health and Nutrition Examination Survey). 22 En general, en América Latina las deficiencias severas de vitamina D (valores <10 ng/mL o 25 mmol/L) son bajas o están muy poco documentadas y se relacionan con manifestaciones clínicas graves.…”
Section: Cuadro Iunclassified
“…The same results were obtained after examination of 974 Brazilian children aged from 2.8 months to 10.4 years. The study showed an association between 25-hydroxyvitamin D average levels and VDR gene Bsm I, FokI, ApaI, TaqαI and Cdx2 mononucleotide polymorphisms, but only mutant allele B in the Bsm I polymorphic site of the VDR gene was the marker related to low serum concentration of 25(OH)D [20].…”
Section: Discussionmentioning
confidence: 90%